2006
DOI: 10.1002/da.20213
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone in patients with bipolar disorder and alcohol dependence

Abstract: Bipolar disorder is associated with very high rates of substance abuse. However, few clinical trials are reported in this population. Naltrexone is effective for alcohol dependence, but its safety and efficacy are not established in patients with bipolar disorder and alcohol dependence. A 16-week, open-label, add-on pilot study of naltrexone was conducted in 34 outpatients with bipolar disorder and alcohol dependence. Assessments included the 17-item Hamilton Rating Scale for Depression (HRSD-17), Young Mania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…While lithium may also show some benefits (level 3),617 it has to be used with caution in heavy drinkers because of potential electrolyte imbalance; and anticonvulsants warrant liver function tests and lipase levels before initiating treatment. Agents for primary alcohol use disorder may also show benefits in BD, such as disulfiram (level 3),688, 689, 690, 691 naltrexone (level 3)692, 693, 694, 695 and gabapentin (level 4) 696, 697. Furthermore, guidelines for pharmacotherapy in alcohol dependence alone can offer some guidance in the absence of comorbidity‐specific trials 698…”
Section: Specific Populationsmentioning
confidence: 99%
“…While lithium may also show some benefits (level 3),617 it has to be used with caution in heavy drinkers because of potential electrolyte imbalance; and anticonvulsants warrant liver function tests and lipase levels before initiating treatment. Agents for primary alcohol use disorder may also show benefits in BD, such as disulfiram (level 3),688, 689, 690, 691 naltrexone (level 3)692, 693, 694, 695 and gabapentin (level 4) 696, 697. Furthermore, guidelines for pharmacotherapy in alcohol dependence alone can offer some guidance in the absence of comorbidity‐specific trials 698…”
Section: Specific Populationsmentioning
confidence: 99%
“…Well controlled studies are required to further investigate the efficacy of naltrexone, alone or in combination with mood stabilizers, against alcohol use disorders in bipolar patients. 38,39 • Aripiprazole. Aripiprazole seems efficient in reducing alcohol use disorders in alcohol-dependent subjects 48,49 and even in bipolar patients.…”
Section: Discussionmentioning
confidence: 99%
“…37 Drugs specifically used for treating alcohol dependence Naltrexone Naltrexone is effective for alcohol dependence, but its safety and efficacy are not established in patients with bipolar disorder and alcohol dependence. Brown and colleagues 38 recently reported the results of a 16-week, open-label, add-on pilot study of naltrexone conducted in 34 outpatients with bipolar disorder and alcohol dependence. Assessments included the 17-item HRSD, YMRS, BPRS and an alcohol-craving scale.…”
Section: Olanzapinementioning
confidence: 99%
See 1 more Smart Citation
“…For example, no controlled clinical trials of any of the three approved medications for treatment of alcohol dependence have been conducted in bipolar patients, despite the fact that almost one half of all bipolar individuals will develop an AUD at some point in their lives. Brown et al [35] found significantly decreased craving and days of alcohol use in a 16-week, open-label trial of naltrexone in 34 bipolar, alcohol-dependent patients, suggesting that controlled trials of this medication are warranted. Acamprosate, the most recently approved medication for alcohol dependence, is currently being tested in an open-label trial at our site, and preliminary results are encouraging.…”
Section: Bipolar Disordermentioning
confidence: 99%